Future e(+)e(-) colliders' sensitivity to Hb(b)over-bar coupling and CP violation - Braguta, V.; Chalov, A.; Likhoded, A. [UNESP]; Rosenfeld, R. [UNESP] (American Physical Soc, 2003)
A complete analysis of the sensitivity to new Hbb̄ couplings from the process e+e- → bb̄vv̄ at the next generation of linear colliders was performed. These new couplings were predicted by many extensions of the Standard Model. The results are comparable to the study performed previously where a global fit analysis for L=500 fb-1 and √s=500 GeV resulted in a relative accuracy of 2.2% in the gHbb Yukawa coupling.
Keywords: Computer simulation; Electron transport properties; Fusion reactions; Mathematical models; Monte Carlo methods; Solid state physics; Colliders sensitivity; Higgs coupling; Higgs sector; Neutrino; Standard model contributions; Electrons